Iris suture fixation of out‐of‐the‐bag dislocated three‐piece intraocular lenses. Issue 6 (7th February 2019) - Armonaite, Laura; Löfgren, Stefan; Behndig, Anders
Abstract: Purpose: To evaluate the efficacy and safety of iris suture fixation of out‐of‐the‐bag dislocated three‐piece intraocular lenses (IOL). Methods: In a retrospective interventional consecutive case series, a chart review was performed in two groups of patients: fourteen patients with a dislocated out‐of‐the‐bag three‐piece IOL that underwent IOL fixation to the iris using the Siepser sliding knot technique (Iris group) and 18 patients with in‐the‐bag dislocation that underwent IOL exchange with a new scleral‐sutured IOL (Exchange group). The Iris and Exchange groups were compared regarding surgical safety and efficacy. The median follow‐up time was 13.5 months [interquartile range (IQR), 10–20] in the Iris group and 12.5 (IQR, 10–14) in the Exchange group. Results: The best corrected visual acuity (BCVA) improved significantly in both groups (p = 0.005 and 0.00006, respectively). No difference in final BCVA was seen between the groups. Significantly less surgically induced astigmatism (p = 0.03) and a lower number of postoperative visits (p = 0.0006) was noted in the Iris group. Considering the type of surgery, there were few complications in the present material. Conclusion: In the study, suturing dislocated three‐piece IOLs to the iris appeared to be an acceptable surgical management with less surgically induced corneal astigmatism and fewer postoperative visits than IOL exchange. A larger study with a longer follow‐up time would be desirable to confirm the results.